β-1,3/1,6-D-glucan of Mycelia Extract Posses Renal Protection Potential and Reduces Nitric Oxide in Obese Subjects - Djanggan Sargowo; Ardian Rizal; Yoga Waranugraha; Anna Fuji Rahimah; Putri Annisa Kamila; Mohammad Rizki Fadlan; Icmi Dian Rochmawati; Cik Kahadi; Yuke Fawziah Kemala; Bunga Bella Pratiwi; Susanti Lara Dewi; Wiwit Nurwidyaningtyas (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Obesity has been widely reported to be associated with loss of kidney function. The efficacy of β-1,3/1,6-D-glucan as a traditional medicine for the improvement of inflammation and vascular status in obesity has known. However, there have been no further studies that prove the effect of β-1,3/1,6-D-glucan in inhibiting kidney injury as an impact of chronic inflammation exposure on obesity. This study aimed to investigate the impact of β-1,3/1,6-D-glucan from mycelia extract supplementation on renal function improvement based on serum nitric oxide (NO), ureum, and creatinine levels.METHODS: This was a randomized control trial study involving 69 obese subjects treated with or without β-1,3/1,6-D-glucan supplementation. The serum NO, ureum, and creatinine levels of the subjects were measured at baseline and post-treatment using enzyme-linked immunosorbent assay (ELISA) and then statistically analyzed with paired T-test.RESULTS: Although slightly decrease, no significant difference was found between the ureum and creatinine level at the baseline and and post-treatment (p=0.806, p=0.306, respectively) after β-1,3/1,6-D-glucan supplementation. Serum NO levels significantly decrease after treatment of β-1,3/1,6-D-glucan (p<0.001).CONCLUSION: Current study concludes that β-1,3/1,6-D-glucan from mycelia extract does not significantly lower urea and creatinine level, however, significantly able to reduce the serum NO concentration in obese subjects. Therefore, β-1,3/1,6-D-glucan from mycelia extract might have the renal protection potential in obesity.KEYWORDS: β-1,3/1,6-D-glucan, Ganoderma lucidum, renal function improvement, obesity